PENGEMBANGAN KOMPETENSI KEPEMIMPINAN DALAM PERSPEKTIF PENDIDIKAN ISLAM (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2025)
This research article aims to analyze the urgency of developing leadership competencies in Islamic education and to formulate effective strategies for creating education leaders based on Islamic values. The main focus of this study is the role of leaders in educational institutions, the characteristics of ideal leadership, and the importance of strengthening competencies to face modern challenges. The methodology used in this research is a literature review with a qualitative approach. The study examines primary and secondary sources, including books, journals, and relevant scholarly articles, while analyzing the concept of educational leadership in Islam based on the teachings of the Qur'an, Hadith, and views of Islamic scholars. The results and findings of this research indicate that developing leadership competencies in Islamic education is crucial to address the complexities of modern challenges. Recommended strategies include strengthening spiritual values and Islamic ethics, improving managerial and technological competencies, continuous leadership training, and implementing the principle of syura (consultation) in decision-making. These findings contribute significantly to the development of adaptive, innovative, and Islam-based educational leadership